A SOCIO-PRAGMATICS ANALYSIS ON ENGLISH DIRECTIVE UTTERANCES IN KING ARTHUR MOVIE MANUSCRIPT - PRASETYO , AGUS EKO (2009)
The objectives of the study are (1) to find the intention from the meaning of the directive utterance in King Arthur movie manuscript, and (2) to find the reason of using directive utterance in King Arthur movie manuscript. This is descriptive qualitative research which takes a document method by selecting the directive utterance in King Arthur Movie Manuscript. The source of the data is taken from King Arthur Movie manuscript. This research employs the socio-pragmatics analysis with use speech act theory to analyze the meaning and SPEAKING theory to analyze the intention directive utterance. The results of the research are to show the intention and reason of using directive utterance. (1) For the intention of the speaker, the writer gets 57% for command, 33% for request, and 10% for suggestion, (2) and to show the reason of using directive utterance, the writer gets 58% in showing power, 25% in showing respect, 5% in giving strong order, and 12% in softening utterance. And there is correlation between the intention and the reason which is influenced each other. In showing power is influenced by command, in showing respect is influenced by request and suggestion, in giving strong order is influenced by request, and in softening utterance is influenced by request and suggestion. It is caused by the speaker’s social status when giving the direction to the addressee.